PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS (Studi pada Perusahaan Sektor Makanan dan Minuman di BEI Tahun 2013-2015) - Enggar Jati Pamungkas, 13.05.51.0231 (Students' Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of work capital efficiences, liquidity and solvability to profitability. Samples were food and baverage companies listed on the Stock Exchange the period 2013-2015 with 14 companies by using purposive sampling method. The analytical method used is multiple linear regression analysis using SPSS.The results of this study prove partially that the work capital negative and significant effect on profitability, while the liquidity and solvability does not effect on profitability. Simultaneously prove that the work capital significant effect on the profitability of the company with a significant level of 0.000< 0.05. Value Adjusted R Square shows the results for 0.609, which means 60.9% are influenced by the value of the profitability, the work capital, liquidity and solvability. While the remaining 39.1% is influenced by other variables outside the study. Keywords: Work Capital Efficiences, Liquidity, Solvability, and Profitability